127k views
4 votes
If f(x) = 3x+5 and g(x) = -2x^2-5x+3 fins (f+g)(x)

User Cowlicks
by
5.3k points

2 Answers

5 votes

Answer:

f(x) + g(x) = -2x^2 - 2x + 8

Explanation:

Given: f(x) = 3x+5 and g(x) = -2x^2-5x+3

Find f(x) + g(x)

f(x) + g(x) = 3x + 5 + (-2x^2 - 5x + 3)

f(x) + g(x) = 5 + -2x^2 - 2x + 3

f(x) + g(x) = -2x^2 - 2x + 8

User Falselight
by
5.2k points
2 votes

Answer:

(f+g)(x) = -2x^2 -2x +8

Explanation:

(f+g)(x) = f(x) +g(x)

= (3x +5) +(-2x^2 -5x +3)

(f+g)(x) = -2x^2 -2x +8

User Adam Martin
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.